2002
DOI: 10.1111/j.0014-3820.2002.tb01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the Socially Polymorphic Sweat Bee Halictus Rubicundus (Hymenoptera: Halictidae)

Abstract: The evolution of sociality in insects holds a central place in evolutionary theory. By examining the phylogenetic patterns of solitary and social behavior and how they correlate with ecological variables, we may identify factors important in the evolution of sociality. In this study, we investigated historical and biogeographical patterns of sociality in a socially polymorphic bee species (one that demonstrates both social and solitary nesting behavior). This unique system allows for a more powerful examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 53 publications
5
106
2
Order By: Relevance
“…Halictids are important bees for studies of social evolution because they show enormous intra- (Sakagami and Munakata, 1972;Yanega, 1988;Eickwort et al, 1996;Richards, 2000;Soucy, 2002) and inter-specific variation in social behavior. Variation in social behavior within species is often linked with altitude and latitude such that populations at high elevation and latitude tend to be solitary, while populations at lower elevation and latitude tend to be eusocial (Sakagami and Munakata, 1972;Packer et al, 1989;Eickwort et al, 1996;Soucy, 2002;Soucy and Danforth, 2002). Diversity in social behavior among species was often thought to be due to frequent independent origins of eusociality in halictids (Eickwort, 1986) but recent molecular studies within and among genera of Halictinae have suggested that reversals from eusociality to solitary nesting may be common (Packer, 1997;Danforth, 1999;Danforth et al, 1999Danforth et al, , 2003Brady et al, 2006).…”
Section: Diversity In Social Behaviormentioning
confidence: 99%
“…Halictids are important bees for studies of social evolution because they show enormous intra- (Sakagami and Munakata, 1972;Yanega, 1988;Eickwort et al, 1996;Richards, 2000;Soucy, 2002) and inter-specific variation in social behavior. Variation in social behavior within species is often linked with altitude and latitude such that populations at high elevation and latitude tend to be solitary, while populations at lower elevation and latitude tend to be eusocial (Sakagami and Munakata, 1972;Packer et al, 1989;Eickwort et al, 1996;Soucy, 2002;Soucy and Danforth, 2002). Diversity in social behavior among species was often thought to be due to frequent independent origins of eusociality in halictids (Eickwort, 1986) but recent molecular studies within and among genera of Halictinae have suggested that reversals from eusociality to solitary nesting may be common (Packer, 1997;Danforth, 1999;Danforth et al, 1999Danforth et al, , 2003Brady et al, 2006).…”
Section: Diversity In Social Behaviormentioning
confidence: 99%
“…Some molecular population genetics studies have been conducted with bees (Tanaka et al, 2001;Soucy and Danforth, 2002;Dick et al, 2004;Cruz et al, 2006;Quezada-Euán et al, 2007;Kraus et al, 2008). However, none of the studies have applied coalescent and more recent phylogeographic methods.…”
Section: Introductionmentioning
confidence: 99%
“…The massprovisioning bee family Halictidae is a key taxon for understanding social evolution. Halictids exhibit multiple evolutionary origins and losses of eusociality, communality, brood parasitism, and solitary nesting (Michener 1974(Michener , 1990Danforth and Eickwort 1997;Wcislo and Danforth 1997;Wcislo 1997Wcislo , 2000Danforth 2002;Soucy and Danforth 2002;Coelho 2002;Richards et al 2003;Danforth et al 2004). In fact, AFR may be greater in mass provisioners.…”
Section: Introductionmentioning
confidence: 99%